Analysis of transforming growth factor β1 gene polymorphisms in patients with systemic sclerosis. Issue 8 (1st August 2002) - Crilly, A; Hamilton, J; Clark, C J; Jardine, A; Madhok, R
Abstract : Objectives: To determine the distribution of transforming growth factor β1 (TGFβ1) genotypes at codon 10 (+869 polymorphism) and codon 25 (+915 polymorphism) in patients with scleroderma (SSc). Differences between diffuse and limited SSc (dSSc and lSSc) were also investigated. Methods: Patients with lSSc (n=89) and dSSc (n=63) were compared with 147 controls. DNA was isolated from peripheral blood and polymorphisms at codons 10 (C/T) and 25 (G/C) of the TGFβ1 gene analysed by polymerase chain reaction and sequence specific oligonucleotide probing. Results: Significantly more patients with SSc than controls carried allele C at codon 10 (controls v SSc, 38% v 48%, χ 2 =8.2, 1df, p=0.004), OR=1.95 (95% CI 1.16 to 3.27). The difference remained when patients with SSc were split into those with limited or diffuse disease, (controls v dSSc, χ 2 =5, 1df, p=0.02 and controls v lSSc, χ 2 =6, 1df, p=0.013). The patients with SSc had significantly more subjects heterozygous at codon 10 (controls v SSc, χ 2 =45, 1df, p<0.0001). Possession of allele C at codon 10 gave an OR=4.8 (95% CI 2.8 to 8.4). No difference in allele frequency was seen between patients with SSc and controls at codon 25. More patients with SSc than controls carried the GG genotype (controls v SSc, 80% v 88%, χ 2 =7, 2df, p=0.027). Possession of allele G gave an OR=1.7 (95% CI 0.5 to 5.9). There was no difference between diffuse and limited disease at either codon. Conclusions: These results suggest that patients with SSc are genetically predisposed to high TGFβ1 production. These polymorphisms do not, however, explain the difference in the clinical phenotypes of limited and diffuse SSc.